WASTE OF ELECTRICAL ENERGY IN LINES AND TRANSFORMERS - Topvoldiyev Nodirbek Abdulhamid o‘g‘li,; Soliyev Muzaffar Mominjan's son, (Лучшие интеллектуальные исследования, 2024)
Abstract; Consumers downloads day , year during changed standing because of power waste The value also changes stands​ In the transformer magnet of the conductor interest , magnet of the conductor free leaving , transformer oil , insulation of paper , varnish from work output wear and tear to account in the transformer energy a waste surface will come . This in the article downloads graph and in transformers electricity energy waste boasting and reduce measures given .